Seasonality affects phytotoxic potential of five native species of neotropical savanna - Pinto, Graciele Fernanda de Souza [UNESP]; Kolb, Rosana Marta [UNESP] (Canadian Science Publishing, 2016)
Phytotoxic secondary metabolites produced by plants have been studied as possible sources of bioher-bicides. However, several environmental factors can change the secondary metabolism of plants, and thus, the production of these compounds. Among these factors, seasonality can be a source of variation in the content of all classes of secondary metabolites. In this study, we evaluated the phytotoxic effect of aqueous extracts of leaves from Byrsonima intermedia A. Juss. (Malpighiaceae), Gochnatia polymorpha (Less.) Cabrera (Asteraceae), Luehea candicans Mart. (Tiliaceae), Miconia chamissois Naudin (Melastomataceae), and Qualea cordata Spreng (Vochysiaceae) (species of the Brazilian savanna), collected both during the dry and the rainy season, on germination and seedling growth of maize and cucumber. The analysed parameters were affected by all leaf extracts collected during both seasons. However, a greater phytotoxic effect was observed when leaves were collected during the dry or during the rainy season, depending on the savanna species studied, on the target species, and on the parameters evaluated. The phytochemical screening of all extracts was also evaluated and allowed the identification of anthraquinones, triterpenoids, saponins, and tannins. The composition of extracts differed between the seasons for all species. This study highlights the importance of considering savanna seasonality when studying the phytotoxicity of the species of this biome.
Keywords: Allelopathy; Aqueous extracts; Cerrado; Phytochemical screening; Secondary metabolism